Meta-Analysis: Learning Model to Increase HOTS of High School Students in Biology Subject - Farras Khirzi Khanifah; Ismail Ismail; Elina Lestariyanti (Bioeducation Journal, 2023)
Higher order thinking skills are one of the skills needed by students in 21st century learning. Many studies have shown that Indonesian students' higher thinking skills are still low. One way to empower students' higher order thinking skills is to choose the right learning model so that learning objectives can be achieved properly. This research is a quantitative study using descriptive methods and analyzing 15 articles written by researchers or students where the learning model research was conducted in Indonesia. The research method used in the articles was quasi-experimental and supported by data needed to calculate the effect size, including mean data, standard deviation, sample size, and hypothesis testing. The articles focused on the influence of the learning model on HOTS of high school students in biology subjects from 2013-2022, which were sourced from journals accredited by Arjuna. The conclusion drawn was that the learning model can empower HOTS students based on the effect size. This research is quantitative research with descriptive method so that it can be concluded that in general the learning model can empower students' HOTS based on effect size. The learning model that is considered to be able to empower students' HOTS with the greatest effect is the jigsaw cooperative type with an effect size value of 1.5. Followed by the multimedia-assisted discovery learning model with an effect size value of 0.72 having a medium effect category. The next moderate effect is a two problem solving cycles model with an effect size value of 0.67.